The role of coronary CT angiography in diagnosis of patent foramen ovale - Kemal Kara; Ali Kemal Sivrioğlu; Ersin Öztürk; Mehmet İncedayı; Muzaffer Sağlam; Serkan Arıbal; Zafer Işılak; Hakan Mutlu (Diagnostic and Interventional Radiology, 2016)

(untitled)
PURPOSE:We aimed to examine the incidence of patent foramen ovale (PFO) and atrial septal aneurysms (ASA) in the Turkish population using coronary computed tomography angiography (CTA); assess the feasibility of coronary CTA for PFO diagnosis by conducting a comparison with transthoracic echocardiography (TTE); and determine the diagnostic role and characteristics of the interatrial tunnel, free flap valve (FFV), and shunts.METHODS:The present study was conducted retrospectively and included a sample of 782 patients. Coronary CTA results for all patients were evaluated for the following parameters: the presence of PFO, the degree of contrast jet (if present due to PFO), ASA existence, free flap valve (FFV) length, and PFO tunnel diameters (1 and 2). Coronary CTA and TTE results for PFO detection were also compared for 19 patients who underwent both procedures.RESULTS:PFO was present in 118 patients (15%). In 19 patients who underwent both CTA and TTE, the shunt was present in 15 patients on TTE compared with nine patients on CTA. The sensitivity and specificity of CTA for shunt existence were 53% (8/15) and 75% (3/4), respectively. FFV was observed on CTA in 118 patients (15%). No significant relationship was observed between shunt existence and FFV length (P = 0.148), or between shunt existence and tunnel diameter-1 (P = 0.638) or diameter-2 (P = 0.058). ASAs were present in 16 patients (2%), while accompanying PFO was present in three patients (2.4%) .CONCLUSION:Coronary CTA constitutes a more practical and efficient alternative to TTE for PFO diagnosis. Further, it allows the clear visualization of anatomical details of the interatrial tunnel, shunts, and associated abnormalities and detects ASAs.